2023
DOI: 10.1039/d2ta07562h
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional carbon dots as cocatalyst and reactor decorating an organic photocatalyst for H2 production from water-splitting in an emulsion

Abstract: Generation of clean hydrogen (H2) energy by photocatalytic water-splitting is a prospective method for solving global energy crisis and environmental pollution and the design of new generation catalysts are expected...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Furthermore, the more negative flat potential compared to PCN could effectively improve the deoxygenation ability of the photoinduced carriers, which is sufficient to trigger the reduction of CO 2 to CO ( E o = −0.53 V vs NHE, pH = 7) . Using the formula E VB = E CB – E g , the corresponding VB potential ( E VB ) for PCN was estimated to be 1.52 V (relative to NHE, pH = 7), and the hole position correction for R1-CQDs/CN was calculated to be 0.99 V. The energy band structures of R1-CQDs/CN and PCN were schematically plotted based on the combined band gap in UV–vis absorption spectra (Figure d) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the more negative flat potential compared to PCN could effectively improve the deoxygenation ability of the photoinduced carriers, which is sufficient to trigger the reduction of CO 2 to CO ( E o = −0.53 V vs NHE, pH = 7) . Using the formula E VB = E CB – E g , the corresponding VB potential ( E VB ) for PCN was estimated to be 1.52 V (relative to NHE, pH = 7), and the hole position correction for R1-CQDs/CN was calculated to be 0.99 V. The energy band structures of R1-CQDs/CN and PCN were schematically plotted based on the combined band gap in UV–vis absorption spectra (Figure d) …”
Section: Resultsmentioning
confidence: 99%
“…45 Using the formula E VB = E CB − E g , the corresponding VB potential (E VB ) for PCN was estimated to be 1.52 V (relative to NHE, pH = 7), and the hole position correction for R1-CQDs/CN was calculated to be 0.99 V. The energy band structures of R1-CQDs/CN and PCN were schematically plotted based on the combined band gap in UV−vis absorption spectra (Figure 5d). 16 EIS was performed to investigate the electrochemical properties of the synthesized samples. The EIS results (Figure 5e) showed that the resistance sequence of the samples is R1-CQDs/CN > R2-CQDs/CN > R3-CQDs/CN > PCN.…”
Section: Fabrication and Optical Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] However, unsatisfactory visible light absorption capacity and easy recombination of photo-generated charge carriers are still the key factors to restrict the reinforcement of photocatalytic performance. 5,6 Numerous studies have shown that well-matched band alignments and effective construction methods of semiconductor materials can largely improve the photocatalytic hydrogen production activity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the coupling of ZnIn 2 S 4 and Ni–Al LDH can predictably construct an efficient heterojunction to promote photocatalytic hydrogen production . Furthermore, the carbon dots (CDs) as a new type of 0D metal-free alternative are often used as electron mediators to enhance the photocatalytic activity in heterojunction catalysts on account of less toxicity, size effect, and excellent charge transfer ability. In addition, CDs as a cocatalyst can effectively utilize the full spectrum of solar light and possess abundant active sites for photocatalytic H 2 generation . Consequently, CDs modify the ZnIn 2 S 4 /Ni–Al LDHs to construct a ternary catalytic system, which can overcome the rapid charge recombination and boost the electron transfer efficiency.…”
Section: Introductionmentioning
confidence: 99%